2009
DOI: 10.5005/jp-journals-10005-1034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Flow Rate, pH, Buffering Capacity, Calcium, Total Protein and Total Antioxidant Levels of Saliva in Caries Free and Caries Active Children—An In Vivo Study

Abstract: Background and objectives: The purpose of this study was to evaluate the relationship between the physicochemical properties of saliva such as flow rate, pH, buffering capacity, calcium level, total protein and total antioxidant levels in caries free and caries active children.Materials and methods: The present study included one hundred and twenty healthy children who were divided into two groups and subdivided according to gender. They were further divided into caries free and caries active children with 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 14 publications
2
30
1
10
Order By: Relevance
“…The association between salivary buffering capacity and dental caries is inconsistent based on previous studies. One publication reported a weak negative association between unstimulated salivary buffering capacity and caries in healthy children ages 7 to 14 years [Prabhakar et al, 2009], whereas another study reported a positive association between stimulated salivary buffering capacity and caries in children ages 9 to 17 years [Cunha-Cruz et al, 2013]. There are two possible explanations for these inconsistencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between salivary buffering capacity and dental caries is inconsistent based on previous studies. One publication reported a weak negative association between unstimulated salivary buffering capacity and caries in healthy children ages 7 to 14 years [Prabhakar et al, 2009], whereas another study reported a positive association between stimulated salivary buffering capacity and caries in children ages 9 to 17 years [Cunha-Cruz et al, 2013]. There are two possible explanations for these inconsistencies.…”
Section: Discussionmentioning
confidence: 99%
“…The second is the method used to measure buffering capacity. Some studies, including our analyses, used the Ericsson method and pH meters [Prabhakar et al, 2009], which is considered the gold standard because of its objectivity, whereas other studies use pH colorimetric strips [Cunha-Cruz et al, 2013] that may introduce bias because of rater subjectivity. Future research should adopt gold standard laboratory methods in measuring buffering capacity and interpret findings carefully based on the type of saliva collected for the study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies which compared calcium and phosphate levels observed that caries‐active children showed lower levels of calcium than caries‐free ones (Prabhakar, Dodawad, & Os, ; Tayab, Rai, & Kumari, ). In caries‐free children, saliva is supersaturated with calcium and acts as a reservoir for these essential ions, favoring the remineralization process.…”
Section: Discussionmentioning
confidence: 95%
“…Benzer şekilde Prabhakar ve ark. aynı yaş grubu 120 çocukta yaptıkları çalışmada aktif çürüklü çocuklarda, çürük dişi olmayan çocuklara göre tükürük akım oranı ve tükürük pH'ının istatistiksel olarak fark olmasa da daha düşük olduğunu saptamışlardır (23).…”
Section: Discussionunclassified